Pengaruh Pengelolaan Dana Desa Terhadap Kesejahteraan Masyarakat Desa Lolak, Kecamatan Lolak, Kabupaten Bolaang Mongondow - Salsia Ulfa Paputungan; Herwin Mopangga; Ivan Rahmat Santoso (Jurnal Economic Resource, 2026)
This study aims to analyze the effect of village fund management on the welfare of the community in Lolak Village, Lolak District, Bolaang Mongondow Regency. The research method used is a quantitative approach with data collection techniques through questionnaires, observation, interviews, and documentation. The research sample consisted of 90 respondents from the Lolak Village community, determined using the Slovin formula. The analysis techniques used include validity test, reliability test, normality test, simple linear regression, t-test, and coefficient of determination test, with the assistance of the IBM SPSS Statistics program. The research instrument was tested for validity and reliability, showing that all instruments were valid and reliable. The results of the simple linear regression analysis indicate a significance value of 0.000 < 0.05, which means that village fund management has a positive and significant effect on community welfare. The coefficient of determination (R²) value of 0.766 shows that village fund management affects community welfare by 76.6%, while the remaining 23.4% is influenced byother factors outside this study